Representative Farms Economic Outlook for the January 2018 FAPRI/AFPC Baseline - James W. Richardson; Joe L. Outlaw; George M. Knapek; J. Marc Raulston; Henry L. Bryant; Brian K. Herbst; David P. Anderson; Steven L. Klose (Texas A&M University, The Agricultural & Food Policy Center (AFPC), 2018)
The Agricultural and Food Policy Center (AFPC) at Texas A&M University develops and maintains data to simulate 94 representative crop, dairy, and livestock operations in major production areas in 29 states. The chief purpose of this analysis is to project the economic viability of those farms by region and commodity for 2018 through 2023. The data necessary to simulate the economic activity of these operations are cultivated through ongoing cooperation with panels of agricultural producers in selected states. The Food and Agricultural Policy Research Institute (FAPRI) provided projected prices, policy variables, and input inflation rates in their preliminary baseline. Under the January 2018 Baseline, 22 of the 63 crop farms are in good liquidity condition (less than a 25 percent chance of negative ending cash by 2023). Five crop farms have between a 25 percent and a 50 percent likelihood of negative ending cash, and the remaining 36 crop farms have greater than a 50 percent chance of negative ending cash. Additionally, 36 of the 63 crop farms are in good equity position (less than a 25 percent chance of decreasing real net worth during the study period). Four crop farms have between a 25 percent and 50 percent likelihood of losing real net worth, and 23 crop farms have greater than a 50 percent probability of decreasing real net worth by 2023. The following discussion provides an overall evaluation by commodity considering both liquidity and equity measures. * FEEDGRAIN FARMS: Eleven of the 23 feedgrain farms are in good overall financial condition. Five farms are classified in marginal condition, and seven are in poor condition. * WHEAT FARMS: Four representative wheat farms are classified in good overall financial condition, four are in marginal condition, and three are in poor condition. * COTTON FARMS: Seven of the 14 cotton farms are classified in good condition, one is in marginal condition, and six are in poor condition. * RICE FARMS: None of the 15 rice farms are projected to be in good financial condition. Four rice farms are projected to be in marginal condition; eleven are in poor condition. * DAIRY FARMS: Thirteen of the 20 dairies are in good overall financial condition. Two dairies are classified in marginal condition, and five are in poor condition. * BEEF CATTLE RANCHES: Two of the 11 cattle ranches are classified in good financial condition, two are in marginal condition, and seven are projected to be in poor condition.
Keywords: 330